Establishment Of Adventitious Root Culture Of Butterfly Pea Plant (Clitoria Ternatea L.) And Its Potential As A Memory Enhancer - Lee, Rui Xuan (2020)
The current study aims to investigate the effects of various auxins in the establishment of in vitro root culture from cotyledon, hypocotyl, cotyledonary node and root explants of C. ternatea L. and to identify the presence of bioactive compounds from the root cultures correlated to memory enhancing properties.